Total Synthesis of Bacterial 5-(3-Indolyl)oxazole Alkaloids: Pimprinols A–C - Szabó, Tímea; Kormány, Róbert; Dancsó, András; Volk, Balázs; Milen, Mátyás (SynOpen, 2019)
Pimprinols A, B, and C are bacterial 5-(3-indolyl)oxazole alkaloids that have been isolated from Streptomyces sp. Lv3–13. In this paper, we report a new synthesis of pimprinol A and the first total synthesis of pimprinol B and pimprinol C. In addition, antipodes of the naturally occurring pimprinols A and C, as well as the racemates of these two alkaloids were also prepared. In the pivotal step, the 1,3-oxazole ring was constructed by a Nicolaou’s modified Robinson–Gabriel cyclization.
Keywords: oxazole; natural products; bacterial alkaloids; pimprinols A–C; total synthesis